ChemInform Abstract: Photoredox‐Catalyzed Reductive Coupling of Aldehydes, Ketones, and Imines with Visible Light. Issue 47 (November 2015) - Nakajima, Masaki; Fava, Eleonora; Loescher, Sebastian; Jiang, Zhen; Rueping, Magnus
Abstract: In the photocatalytic protocol tributylamine acts not only as an electron donor but also serves to activate the substrates, thus allowing the coupling of aldehydes, ketones, and imines under mild conditions.